STRATEGI KOMUNIKASI PEMASARAN PT.PLN (Persero) UNIT LAYANAN PELANGGANG SIMPANG TIGA DALAM MENINGKATKAN PENDAPATAN MELALUI PELANGGAN INDUSTRI - Nurfajar Ronika; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
PT. PLN (Persero)Unit Layanan Pelanggan Simpang Tiga (ULP) is a branch office of PT. PLN (Persero) which has the most industrial customers in the Pekanbaru area. Throughout 2017, PT. PLN (Persero) ULP Simpang Tiga has experienced a decline in revenues earned from industrial customers. In addition, since the enactment of Law No. 30 of 2009 concerning Electricity, PT. PLN (Persero) has competitors from the private sector. This makes PT. PLN (Persero) ULP Simpang Tiga carries out marketing communication strategies that can maintain and increase its revenue. The purpose of this study was to determine the marketing communication strategies used by PT. PLN (Persero) ULP Simpang Tiga.This study uses a qualitative method with a descriptive approach, with data collection techniques namely through interviews, observations, and documentation, with the number of informants totaling 8 people who fit the criteria determined through purposive sampling. The data analysis technique used in this study is the model Miles and Huberman, and the data validity checking technique is the extension of participation and triangulation. The results of the study indicate that to increase revenue from industrial customers PT. PLN (Persero) ULP Simpang Tiga uses marketing communication strategies direct marketing, sales promotion, and personal selling. In the strategy of direct marketing PT. PLN (Persero) ULP Simpang Tiga carries out marketing through social media and print media. Social media used in the form of Facebook, Instagram, E-mail, and WhatsApp as well as telephone lines then printed media used in the form of letters used to offer programs from PLN. Marketing communication strategy in the form of sales promotion carried out by PT. PLN (Persero) ULP Simpang Tiga in the form of discounts or discounts, product warranties and patronage awards for industrial customers who use the program from PLN. And the last marketing communication strategy is personal selling conducted by PT. PLN (Persero) ULP Simpang Tiga in the form of direct visits to the offices of industrial customers and PT. PLN (Persero) ULP Simpang Tiga also provides services for industrial customers who come directly to the office of PT. PLN (Persero) ULP Simpang Tiga or make a meeting at the cafe. In addition, PT. PLN (Persero) ULP Simpang Tiga also held a customer gathering to conduct marketing directly to the leadership of the company.